Gegeplak as Local Food Acculturation of Betawi and Sunda in the Hajat Bumi Tradition in Hegarmukti Village - Marsindi Marsindi; Dewi Turgarini; Heni Pridia Rukmini Sari (Gastronomy Tourism Journal, 2023)
Bekasi Regency is an area that is directly adjacent to DKI Jakarta so that it can be seen that Sundanese culture in Bekasi Regency is acculturated with Betawi culture, especially in food, ranging from local food offerings to the Hajat Bumi tradition. The Hajat Bumi tradition is a tradition that is carried out every year after the harvest period as a form of gratitude for the harvest. The purpose of this study is to identify local foods that are acculturated with Betawi and Sundanese cultures in the Hajat Bumi Tradition. The method in this study is a descriptive qualitative method utilizing an ethnographic approach with data collection methods of interviews, observations and literature studies. The results of this study show that the main factor in the occurrence of acculturation is because Bekasi Regency is dominated by Sundanese and Betawi tribes, facilitating the easy influence of culture, especially food, each other. The main difference between gegeplak Kabupaten Bekasi and geplak Betawi is in the name and function. Gegeplak in Bekasi Regency is used as part of Sasajen or food offerings while in Betawi it only exists at moments such as Eid al-Fitr. The difference between gegeplak Bekasi Regency and gegeplak Karawang lies in the shape and color, gegeplak Karawang is given a variety of colors and smaller shapes compared to gegeplak Bekasi Regency.